The Nonsteroidal Farnesoid X Receptor Agonist Cilofexor (GS‐9674) Improves Markers of Cholestasis and Liver Injury in Patients With Primary Sclerosing Cholangitis. Issue 3 (10th March 2019) - Trauner, Michael; Gulamhusein, Aliya; Hameed, Bilal; Caldwell, Stephen; Shiffman, Mitchell L.; Landis, Charles; Eksteen, Bertus; Agarwal, Kosh; Muir, Andrew; Rushbrook, Simon; Lu, Xiaomin; Xu, Jun; et al.
Abstract : Primary sclerosing cholangitis (PSC) represents a major unmet medical need. In a phase II double‐blind, placebo‐controlled study, we tested the safety and efficacy of cilofexor (formerly GS‐9674), a nonsteroidal farnesoid X receptor agonist in patients without cirrhosis with large‐duct PSC. Patients were randomized to receive cilofexor 100 mg (n = 22), 30 mg (n = 20), or placebo (n = 10) orally once daily for 12 weeks. All patients had serum alkaline phosphatase (ALP) > 1.67 × upper limit of normal and total bilirubin ≤ 2 mg/dL at baseline. Safety, tolerability, pharmacodynamic effects of cilofexor (serum C4 [7α‐hydroxy‐4‐cholesten‐3‐one] and bile acids), and changes in liver biochemistry and serum fibrosis markers were evaluated. Overall, 52 patients were randomized (median age 43 years, 58% male, 60% with inflammatory bowel disease, 46% on ursodeoxycholic acid). Baseline median serum ALP and bilirubin were 348 U/L (interquartile range 288‐439) and 0.7 mg/dL (0.5‐1.0), respectively. Dose‐dependent reductions in liver biochemistry were observed. At week 12, cilofexor 100 mg led to significant reductions in serum ALP (median reduction −21%; P = 0.029 versus placebo), gamma‐glutamyl transferase (−30%; P < 0.001), alanine aminotransferase (ALT) (−49%; P = 0.009), and aspartate aminotransferase (−42%; P = 0.019). Cilofexor reduced serum C4 compared with placebo; reductions in bile acids were greatest with 100 mg. Relative reductions in ALP were similar between ursodeoxycholic acid–treated and untreated patients. At week 12, cilofexor‐treated patients with a 25% or more relative reduction in ALP had greater reductions in serum alanine aminotransferase, aspartate aminotransferase, gamma‐glutamyl transferase, tissue inhibitor of metalloproteinase 1, C‐reactive protein, and bile acids than nonresponders. Adverse events were similar between cilofexor and placebo‐treated patients. Rates of grade 2 or 3 pruritus were 14% with 100 mg, 20% with 30 mg, and 40% with placebo. Conclusion: In this 12‐week, randomized, placebo‐controlled study, cilofexor was well tolerated and led to significant improvements in liver biochemistries and markers of cholestasis in patients with PSC.